The Ethics of Using Artificial Intelligence (AI) in Learning in a Philosophical Perspective - Irnawati, Irnawati; Fatmawati, Yuni; Mahardhika, I Ketut; Suratno, Suratno (International Journal of Education, Information Technology, and Others, 2024)
This article discusses the ethical use of artificial intelligence (AI) in education from a philosophical perspective. AI has revolutionized education by bringing personalization of learning, administrative efficiency, and development of 21st century skills. However, its application presents ethical challenges, including access inequality, data privacy, algorithm bias, and technology dependency. Through literature analysis, this article uses ethical theory approaches, such as utilitarianism, deontology, and virtue ethics, to evaluate the moral and social impact of AI in education. The results show the importance of an ethical framework based on the principles of fairness, transparency, privacy, accountability, and beneficence. This framework aims to support the fair and inclusive use of AI without diminishing the role of humans. This article emphasizes that AI should be equipped with continuous ethical oversight to safeguard human values and ensure its positive impact on education in a holistic manner.